2006
DOI: 10.1254/jphs.fp0060324
|View full text |Cite
|
Sign up to set email alerts
|

Blockade by NIP-142, an Antiarrhythmic Agent, of Carbachol-Induced Atrial Action Potential Shortening and GIRK1/4 Channel

Abstract: Abstract. Mechanisms for the atria-specific action potential-prolonging action of NIP-142 ((3R*,4S*)-4-cyclopropylamino-3,4-dihydro-2,2-dimethyl-6-(4-methoxyphenylacetylamino)-7-nitro-2H-1-benzopyran-3-ol), a benzopyran compound that terminates experimental atrial arrhythmia, was examined. In isolated guinea-pig atrial tissue, NIP-142 reversed the shortening of action potential duration induced by either carbachol or adenosine. These effects were mimicked by tertiapin, but not by E-4031. NIP-142 concentration-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Concentration-dependent inhibition of the current was observed in both types of cells: the inhibitory effect was 8-10 times potent than those on IKur in both cells (Table 2). The inhibition of GIRK1/GIRK4 current amplitude in HEK293 cells by 0.1, 1 and 10 μmol/L NIP-142 was 28.9 ± 5.3%, 58.4 ± 6.2% and 76.8 ± 8.4%, respectively (Matsuda et al, 2006). The inhibition was independent from the voltage dependency of the voltage clamp pulse.…”
Section: Effect Of Nip-142 On the Membrane Currentsmentioning
confidence: 82%
See 2 more Smart Citations
“…Concentration-dependent inhibition of the current was observed in both types of cells: the inhibitory effect was 8-10 times potent than those on IKur in both cells (Table 2). The inhibition of GIRK1/GIRK4 current amplitude in HEK293 cells by 0.1, 1 and 10 μmol/L NIP-142 was 28.9 ± 5.3%, 58.4 ± 6.2% and 76.8 ± 8.4%, respectively (Matsuda et al, 2006). The inhibition was independent from the voltage dependency of the voltage clamp pulse.…”
Section: Effect Of Nip-142 On the Membrane Currentsmentioning
confidence: 82%
“…The delayed rectifier current has three components: the rapid component, I Kr , the slow component, I Ks and the ultrarapid component, I Kur . The effects on I Kr , I Ks and I Kur were examined with HEK293 cells expressing the human ether a-go-go (hERG) channel, the human KCNQ1/KCNE1 channel and human K v 1.5 channel, respectively (Matsuda et al, 2001(Matsuda et al, , 2006. NIP-142 concentration-dependently inhibited these three channel currents.…”
Section: Effect Of Nip-142 On the Membrane Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In guinea-pig myocardium, we have shown that the acetylcholine-activated potassium current is present in the atrial myocardium in the absence of muscarinic receptor stimulation, and that NIP-142 prolongs action potential duration and effective refractory period through blockade of this current. 6,8) Such effect was not observed in the ventricle which may explain the atria-selective nature of NIP-142. Also in the case of the mouse atrium, NIP-142, as well as tertiapin, a peptide inhibitor of the acetylcholine-activated potassium channel, prolonged the late repolarization phase (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…NIP-142 was shown to inhibit the acetylcholine-activated potassium channel current and prolong the action potential duration in guinea-pig atrial myocardium. 8) Thus, although further investigation is necessary for definitive conclusions, the most likely explanation for the effects of NIP-142 in mouse atria at present is that NIP-142 prolongs the atrial action potential duration through blockade of the transient outward current as well as the acetylcholine-activated potassium current, and produces prolongation of the effective refractory period.…”
Section: Resultsmentioning
confidence: 99%